Continuous crystallisation of organic salt polymorphs - McGinty, John; Svoboda, Vaclav; MacFhionnghaile, Pol; Wheatcroft, Helen; Price, Chris J.; Sefcik, Jan (Frontiers in Chemical Engineering, 2022)
Organic salt crystallisation is of great importance to the pharmaceutical industry as many pharmaceutical products are sold as salts with salt formation being an essential step in drug development. The model compound used in this work is the polymorphic organic salt ethylenediammonium 3,5-dinitrobenzoate (EDNB) which is the 2:1 salt of 3,5-dinitrobenzoic acid with ethylenediamine. Crystallisation of the two EDNB polymorphs, the stable monoclinic form and the metastable triclinic form, was performed in both semi-batch and continuous processes using continuous mixing approaches. It was demonstrated that continuous mixing approaches, using various types of continuous mixers (co-axial, Ehrfeld, X-mixer) can be used to crystallise the EDNB salt with consistent yield and particle size distribution while achieving control over polymorphic form. The experiments were designed with use of a solution speciation model which provided process understanding and insight to guide development of salt crystallisation processes.